Classification and Fractal Characteristics of Limestone Fragments Obtained in Conventional Compression and Cyclic Loading Tests under Uniaxial and Triaxial Conditions - Rui Yang; Xiaodi Wang; Hao Zha; Xiuzhang Yang; Yang Zhang; Gang Huang; Yongjie Yang (Advances in Materials Science and Engineering)
The mechanical response characteristics of rocks under cyclic loading conditions are crucial factors for evaluating and analyzing the stability of rock mass during underground excavation. In this study, based on fractal theory and a series of tests using the MTS815.02 rock mechanics test system, the classification and fractal characteristics of limestone specimen fragments are investigated. The results show that limestone specimens subjected to cyclic loading can generate more small-sized fragments than conventional compression, but the large-fragment-producing abilities of the two tests exhibit small difference. The mass fraction of the fragments in the cyclic loading test is obviously greater than that in the conventional test when the fragment size is less than 4.75 mm; however, only a small difference is observed between the cyclic loading tests with frequencies of 0.25 and 0.5 Hz. In the same type of test, a confining pressure is helpful in reducing the fragmentation of limestone specimen. As the size interval decreases, the shapes of limestone fragment transition from rectangular to long slice and then to square. The results also indicate that the confining pressure has a significant influence on the size-quantity and size-mass fractal dimensions of limestone fragments. The former has a positive correlation with the confining pressure, whereas the latter decreases with confining pressure. The conclusions obtained in this investigation can enrich the theoretical research on the failure response and mechanism of rock under cyclic loading conditions.